SOCIAL TIES AND MARKERS OF INFLAMMATION: DO PSYCHOLOGICAL AND EMOTIONAL WELL-BEING MEDIATE EFFECTS?. (11th November 2018) - Stokes, J
Abstract: Prior research has established the importance of social integration and experiences of daily discrimination for various aspects of well-being, including self-esteem and positive affect. Indeed, both supportive and straining aspects of social ties have even been linked with adults' reports of physical health, as well. Using data from the National Survey of Midlife Development in the United States (MIDUS) Refresher (2011–2014) and the MIDUS Refresher Biomarker Project (2012–2016), this study extends prior research to examine whether social integration and daily discrimination are linked with physiological inflammatory biomarkers, and whether any such effects are mediated by self-esteem and/or positive affect. The sample includes 746 adults aged 25–76 who participated in both components of the MIDUS Refresher. Structural equation modeling (SEM) results indicate that both social integration and daily discrimination were significantly linked with inflammatory biomarkers, with positive affect and self-esteem serving as pathways for indirect effects. Positive affect significantly predicted lower sICAM-1 levels, while self-esteem significantly predicted lower Interleukin-6 levels. Daily discrimination was significantly directly associated with higher sICAM-1 and C-reactive protein levels. Further, daily discrimination was significantly indirectly linked with higher Interleukin-6 levels via its influence on self-esteem. Social integration was significantly indirectly linked with lower sICAM-1 levels via its influence on positive affect, and with lower Interleukin-6 levels via its influence on self-esteem. These findings highlight psychological and emotional well-being as mechanisms connecting social ties and day-to-day interactions with physiological stress responses. I discuss the implications of these results for future research concerning social ties and physical health.